Evaluation of vitamin D, vitamin B12 and Hemoglobin HbA1c levels in patients with type 1 diabetes mellitus - Kamile Yucel; Berna Bayir; Hatice Yildirim (Medicine Science, 2022)
We aimed to evaluate the Vitamin D, Vitamin B12 and Hemoglobin A1c Levels in patients with T1DM. This study is a retrospective cross-sectional study. We classified patients as [Med-Science 2022; 11(4.000): 1603-7]